Kontekstualisasi Kebijakan Pengembangan Koleksi Dalam Memenuhi Kebutuhan Informasi Pengguna (Studi Kasus di Perpustakaan UIN Sunan Kalijaga Yogyakarta) - Iskandar, Iskandar (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
This study titled Contextualization of Collection Development Policy to fulfillÂ the information need of users: A case study in the library of State Islamic University of Sunan Kalijaga Yogyakarta, researcher analyzed how contextualization of collection development policy of the Library of State Islamic University of Sunan Kalijaga have an impact to the suitability of information served to the users. This study uses qualitative descriptive approach. From the results of research conducted by the researcher, the result is the contextualization of collection development policy carried out by the Library of State Islamic University of Sunan Kalijaga Yogyakarta, is not maximized, because the librarian have not been given full authority in the management of the library budget.